Kalam science and its urgency in the context of religious moderation (Islam Wasathiyah) - Eliza, Eliza; Karni, Awis; Ashadi, Andri; Hadi, Rahmad Tri (Universitas Ahmad Dahlan, 2024)
The varying perspectives held by Indonesian society often lead to conflicts between religious groups, particularly when one group believes that safety and truth are exclusive to its membership. It is possible to address this issue by deeply studying Islam and adopting a moderation and tolerance mindset. The Islamic concept of moderation is known as rahmatan lil alamin. Islam's spiritual underpinnings ensure global peace, harmony, and fraternity among all peoples. A shallow understanding of religion causes people to act towards extremes, believing that they are right and others are wrong. The results of this research show that kalam science can be a means of contributing to a person's actions and behaviour in understanding and realising the sense of diversity that is khilafiah, and give birth to a moderate attitude so that Kalam Science can present a context and paradigm for religious moderation, and not be quick to place blame on others. This is because a person with a deeper understanding of religion (theology) is more knowledgeable of societal inequalities in both the religious and social domains.